Introduction of a siphon pump for large-scale irrigation in East Belesa district, Ethiopia - Alemayehu, Atikilt Abera; Desalegn, Melkie; Hunie, Melaku (International Journal on Food, Agriculture and Natural Resources, 2024)
Ethiopia's food supply and economy in general are largely dependent on rain-fed agriculture, which is persistently affected by drought. To counteract the recurrent drought, different water harvesting and irrigation schemes were constructed. Similarly, Dengora Earth dam was constructed in East Belesa district in central Gondar, Ethiopia. However, the dam was not functional for a long time due to the silting of the bottom sediment and water outlets. Therefore, the study aimed to transfer water over the dam crest using a low-cost siphon pump for large-scale irrigation. As a result, three siphon pumps with a diameter of three inches were installed. The discharge capacity of one siphon pump in a given reservoir is about 20.80 l/s. In reverse, the motor pump works for about 10 hours with an average fuel consumption of 35 litres per day. The technology was evaluated based on costs, efficiencies, and technical requirements through the wide participation of stakeholders. The siphon pump was selected and well accepted by the beneficiaries, and their feedback was gathered as the technology could be scaled to irrigate more areas without fuel and related costs. Therefore, a siphon pump is feasible for Dengora Earth Dam and similar reservoirs.